The Impact of Implementing Social Commerce Marketing on Purchasing Jambi Batik Products - Sari, Novita; Rosyid, Garry Yuesa; Setiawan, Wahyu Juari; Perdana Siregar, Ade (Dinasti International Journal of Digital Business Management, 2025)
The challenge for business people in the era of globalization is to be able to survive and have an advantage over competition. Consumers' consumption patterns have shifted from shopping at conventional stores to online stores. Social commerce marketing is the best marketing strategy to do at this time considering that with internet use there is more focus on social media. Jambi Batik products are typical products from Jambi Province because their motifs and colors are the first impression for consumers when choosing a product. In online transactions, consumers need confidence that Batik Jambi products meet their expectations. Marketing strategies that implement social commerce marketing need to have support from communication channels through social presence from customers to help attract new or existing consumers to make repeat purchases. The objectives of this research are (1) to examine social commerce marketing on continuous purchase intention; (2) examine the influence of social commerce marketing on social presence; (3) examine the influence of social presence on continuous purchase intention; (4) examine the role of social presence as a mediating influence of social commerce marketing on continuous purchase intention. The research is research using quantitative methods, where data is collected through surveys and distribution of questionnaires and data measurement is based on measurement instruments from questionnaire data obtained from respondents. The analytical method used is Structural Equation Modeling (SEM) measurements using SmartPLS software. The measurement method used is Structural Equation Modeling (SEM) which utilizes data processing tools, namely SmartPLS software